IMPLEMENTASI INOVASI LAYANAN MOBIL KELILING (STUDI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TRENGGALEK) - Dika Yoga Pratama; Tjitjik Rahaju (Universitas Negeri Surabaya, 2022)
The Department of Population and Civil Registration of Trenggalek Regency created an innovation in the field of population administration, namely a round-trip car based on a ball pick-up that provides easy service for the administration of population administration in villages and sub-districts. The purpose of this study is to describe the application of mobile car innovation carried out by the Trenggalek Regency Population and Civil Registration Office. This type of research uses descriptive research with a qualitative approach. This study uses four success factors of implementation by Edwards III which include communication, resources, disposition and organizational structure. The results of the study indicate that the communication indicator, the service provider has carried out socialization with the community through the village apparatus. Coordination is also well established between agencies, sub-districts, and villages when implementing mobile car services. Resource Factors, for human resources already have qualified and competent officers in their fields. However, for the resources of the tools used, there needs to be rejuvenation to improve the quality of service. There must also be an increase in budget resources to maximize mobile car services. Disposition factor, the commitment that has been established from the service implementer who performs their duties according to the SOP. The sub-district, the village which also made the program a success and the community who felt the positive impact of the mobile car innovation. Furthermore, the organizational structure factor that has been well structured makes it easier to coordinate between lines in carrying out population administration services. There are facilities and infrastructure constraints, such as mobile cars, which only amount to two operational cars, which are not sufficient for recording, judging from the topographical conditions of the mountainous Trenggalek district. There is a need for the addition of a new operational car to pick up the ball to reach remote areas.